Quasi-optical analysis of a double reflector microwave antenna system. Issue 2 (5th March 2018) - Pereira, Ricardo A. M.; Carvalho, Nuno Borges; da Cunha, José Pinto
Abstract : By using quasi-optical tools, it is possible to approximate microwave radiation to Gaussian beams, which enables the study of its propagation and coupling to different components. Hence, their usefulness for wireless power transfer and rapid system design. In this paper, a system composed of two reflectors is analyzed both theoretically and by discussing two cases where quasi-optical tools were applied. The near- and far-field regimes were considered and corresponding frequencies of operation, beam radius, and radius of curvature were computed.